2015
DOI: 10.1002/chem.201503355
|View full text |Cite
|
Sign up to set email alerts
|

Facile Installation of 2‐Reverse Prenyl Functionality into Indoles by a Tandem N‐Alkylation–Aza‐Cope Rearrangement Reaction and Its Application in Synthesis

Abstract: An unprecedented tandem N-alkylation-ionic aza-Cope (or Claisen) rearrangement-hydrolysis reaction of readily available indolyl bromides with enamines is described. Due to the complicated nature of the two processes, an operationally simple N-alkylation and subsequent microwave-irradiated ionic aza-Cope rearrangement-hydrolysis process has been uncovered. The tandem reaction serves as a powerful approach to the preparation of synthetically and biologically important, but challenging, 2-reverse quaternary-cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 56 publications
0
10
2
Order By: Relevance
“…The authors argue that the mechanism includes the europium­(III)-catalyzed coupling of the oxime with MeO 2 CCCCO 2 Me to give 223 (b and c). The metal center could accelerate the imine–enamine tautomerization (d) for further aza-Cope rearrangement (for recent works, see refs ), leading to 1-imine-4-one (e), which subsequently undergoes heterocyclization to 222 (f). The reaction proceeded in substantially lower yields in ClCH 2 CH 2 Cl or THF under reflux for 24 h and did not proceed in MeCN and MeOH.…”
Section: Metal-involving Reactions Of Oximes Leading To Carbo- and He...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors argue that the mechanism includes the europium­(III)-catalyzed coupling of the oxime with MeO 2 CCCCO 2 Me to give 223 (b and c). The metal center could accelerate the imine–enamine tautomerization (d) for further aza-Cope rearrangement (for recent works, see refs ), leading to 1-imine-4-one (e), which subsequently undergoes heterocyclization to 222 (f). The reaction proceeded in substantially lower yields in ClCH 2 CH 2 Cl or THF under reflux for 24 h and did not proceed in MeCN and MeOH.…”
Section: Metal-involving Reactions Of Oximes Leading To Carbo- and He...mentioning
confidence: 99%
“…α-Oxoaldoximes and cyanoximes R 1 C­(O)­C­(R 2 )NOH ( 341 ) reacted with the vinylboronic acids R 4 CHC­(R 3 )­B­(OH) 2 (5-fold excess; 342 ) in the presence of Cu­(OAc) 2 (1 equiv), pyridine (3 equiv), and Na 2 SO 4 (6.6 equiv) to obtain oxazine N -oxides 343 (in ClCH 2 CH 2 Cl, RT, 2 h, 27–94%; Scheme , a) . It is argued that this reaction proceeds via the initial copper­(II)-mediated oxidative N -vinylation of oxime 341 (b; see section for details) followed by Cope rearrangement of the formed nitrone (c) (for recent works, see refs ) …”
Section: Metal-involving Reactions Of Oximes Leading To Carbo- and He...mentioning
confidence: 99%
“…When CDMT was added in one portion to a mixture of 1-Boc-gramine 2j and 3a in MeCN in the presence of LiCl and i -Pr 2 EtN, the substitution reaction proceeded at room temperature to afford the desired product 4ja in 39% yield (Table , entry 1). Careful analysis of the crude mixture suggested that 1-Boc-(3-chloromethyl)­indole ( 5j ) was still present (33% yield); however, it could not be isolated because of its instability . As iodide salts can catalyze nucleophilic substitution reactions, LiI was employed in the reaction instead of LiCl (entry 2); however, the yield of 4ja was unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Bromide 7 was obtained in three steps from commercially available 1 H -indole-3-carbaldehyde following literature procedures. 29 All chromatography techniques were performed with indicated solvents and a 300–400 mesh silica gel (solvent abbreviation: PE = petroleum ether). The reaction progress was monitored using a TLC plate under a UV light (254 nm).…”
Section: Methodsmentioning
confidence: 99%